A pristine-UNIONS view on the Galaxy: kinematics of the distant spur feature of the Sagittarius stream traced by blue horizontal branch stars - Bayer, Manuel; Starkenburg, E.; Thomas, G. F.; Martin, N. F.; Helmi, A.; Byström, A.; Boer, T. de; Alvar, E. Fernández; Gwyn, S.; Ibata, R.; Jablonka, P.; Kordopatis, G.; et al. (Astronomy and astrophysics, 2025)
Context. Providing a detailed picture of the Sagittarius stream offers important constraints on the build-up of the Galactic halo as well as its gravitational potential at large radii. While several attempts have been made to model the structure of the Sagittarius stream, no model has yet been able to match all the features observed for the stream. Moreover, for several of these features, the observational characterisation of their properties is rather limited, particularly at large distances. Aims. The aim of this work is to investigate the kinematics of the Sagittarius stream’s outermost spur feature using blue horizontal branch (BHB) stars. Methods. Candidate BHB stars were selected by combining two approaches: one capitalising on Pan-STARRS1 3Π griz and u photometry taken as part of UNIONS, the other using Pristine Survey CaHK and SDSS ugr photometry. Follow-up optical spectra were obtained using ESO/VLT/FORS2 to confirm their BHB nature and obtain line-of-sight (LOS) velocities. Results. Of our 25 candidates, 20 stars can be confirmed as bona fide BHB stars. Their LOS velocities, together with the 3D positions of these stars qualitatively match well with Sagittarius model predictions and trace the outer apocentre of the trailing arm and its spur feature very clearly. The quantitative offsets that are found between our data and the different models can be used to provide information about the Galactic gravitational potential at large distances. We present a first tentative analysis in this direction, and show that a realistic state-of-the-art N-body simulation of Sagittarius would provide better agreement with our observations if the enclosed mass of the Milky Way within 100 kpc were lowered to (5.3±0.4) × 10 11 M⊙ (versus (5.6±0.4) × 10 11 M⊙). Conclusions. Our selection of bona fide BHB stars provides a new view on the outermost structure in 3D positions and LOS velocities of the Sagittarius debris.
Gesehen am 05.02.2026